Mercury (Hg) and Copper (Cu) Analysis of Sea Cucumber Paracaudina australis Crackers from Kenjeran Surabaya using Atomic Absorption Spectroscopy - Wulandari, Alissa Wahidah; Yuliani, Dewi; Adi, Tri Kustono (ALCHEMY, 2015)
Sea cucumber Paracaudina australis crackers is one of the sea foods processed which highly produced and consumed at Kenjeran Surabaya. The research aims to measure concentration of mercury and copper in fried and un-fried sea cucumber Paracaudina australis, Crackers collected from three supplier at Kenjeran Surabaya Using Atomic Absorption S Spectroscopy (AAS). The six sample were oxidized using oxidator agentsÂ  of HNO3 Pa, H2SO4 Pa, H2O2 Pa (6:2:1) under wet-closed digestion for Hg analysis and wet-opened digestion for Cu analysis. Vapor generation Accessory (VGA-AAS) was applied for measuring Hg concentration while flame AAS for Cu. The research indicated that Hg concentration in sea cucumber crackers were 0,058; 0,0149; 0,108 ppb (un-fried crackers) and 0,078; 0,074; 0,061 ppb (fried crackers) Cu concentration in sea cucumber crackers was measured as 2,037; 3,05; 3,16 ppm (un-fried crackers) and 1,164; 1,589; 1,924 ppm (fried crackers).